DIVERSIFIKASI PRODUK PANGAN LOKAL DALAM MENUNJANG KETAHANAN PANGAN NASIONAL (PEMBUATAN BROWNIES TEPUNG UBI JALAR) - Nur Inayah, Astrina; Rukmelia, Rukmelia; Haryono, Iranita; Padapi, Astrini; Fitriani, Fitriani (Jurnal Pengabdian Masyarakat Sabangka, 2024)
The problem with the Asoka Women's Farmers Group (KWT) is the lack of access to agricultural education and training that KWT requires. The main problem in diversifying local food products is the consistent availability of raw materials. Variability in raw material quality can be a problem. The aim of the activity is to carry out mentoring activities, namely the diversification of local food products in supporting national food security by making sweet potato flour brownies. The method used is the counseling and training method for making sweet potato flour brownies. The partners involved in this activity are the Asoka Women's Farmers Group. Implementation of outreach activities on diversification of local food products to support national food security and training on making sweet potato flour brownies, on June 17 2023. The results of this activity increased knowledge from community activity in the activity, as well as the number of people who took part in the activity. The conclusion of this activity is that the implementation of the activity ran smoothly in collaboration with Kadidi Village officials. Participants were very enthusiastic in taking part in the activity.